An orientation measurement system of the two-DOF permanent magnet spherical motor based on hall ring detectors. (January 2020) - Li, Guidan; Feng, Jiaxu; Li, Bin; Li, Hongfeng
Graphical abstract: Highlights: The orientation measurement system is based on magnetic field of spherical motor. Hall ring detectors are used to measure the magnetic field of the spherical motor. The geometry intersection feature is utilized to calculate the rotor position. An orientation measurement system is established and validated by experiments. Abstract: This paper proposes an orientation measurement system based on Hall ring detectors used in two-DOF permanent magnet spherical motor (PMSM). Given the magnetic field of the PM rotor, the method uses ellipses to fit the magnetic field contour. To utilize the ellipses proposed, form a ring detector by multiple Hall sensors, then the position difference between the magnetic pole and the ring detector is solved according to the geometry intersection feature. Because only one Hall ring detector can't cover magnetic field of the entire rotor surface, a configuration strategy for multiple ring detectors is advised, and the idea of the strategy is inspired by Monte Carlo method. Because of complexity of the existing multiple ring detectors and multiple PM poles, the overall orientation determination algorithm is sorted out. According to given angular trajectories, effectiveness of the orientation determination algorithm is verified by simulation and experiment with three-axis rotary table respectively.